PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA DI KANTOR BADAN PUSAT STATISTIK KOTA PALOPO - Cindy Putri Salsabila Kadir; Rima Wulandari; Natasya Yusri; Jubertu Tanawali; Erwina Erwina (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the effect of training and work discipline on work productivity at the Office of the Central Bureau of Statistics in Palopo City simultaneously and partially. This research was conducted on 19 employees of the Central Bureau of Statistics Office of Palopo City with a quantitative approach. Data were obtained using a questionnaire that was distributed randomly and measured with a Likert scale unit. The data obtained were then analyzed using multiple regression. The results of the study show that: (1) Training and work discipline have a significant effect on the work productivity of employees at the Office of the Central Bureau of Statistics for the City of Palopo. (2) Training has a significant effect on employee work productivity at the Office of the Central Bureau of Statistics for the City of Palopo. (3) Work discipline does not significantly influence the work productivity of employees at the Office of the Central Bureau of Statistics for the City of Palopo.